A Study About Islamic Law of Marriage and Divorce: Challenges and Obstacles in Achieving Gender Equality in Muslim Personal Law (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The problem of inequality for women is more social than legal. Asregards to the law, except for personal matters, inequalities in the provisionsof law are hardly found. Personal matters, however, are regulated by religiouslaws or customs. In the legal system though these laws or customs areincorporated separately under the head of Personal Law, these are not, however,as a whole derived from religious laws or customs. Some changes throughintroducing enactments or promulgating ordinances were made in theirapplication. Still, these have been insufficient to establish equality betweenwomen and men. This paper shows how Muslim women are being treated with regardto their Personal Law, in particular Marriage and divorce law. Prevailingsocial constructions of gender are still a fundamental obstacle in realizingthe demands of existing law. In order to remove inequalities and impose justice,particularly in marriage-related matters.